Análise da interoperabilidade entre os programas computacionais Autodesk Revit e EnergyPlus para a simulação térmica de edificações - Queiróz, Gabriel Ramos de (2016)
The Autodesk Revit software has been increasingly used in architecture due to the advantages brought about by the incorporation of BIM technology, which combines all the information representing a real building into a single virtual model. However, its capabilities have not yet been fully explored, such as in building simulations, for which Revit lacks detailed thermal analytical features. Thus, this study aims to examine the reliability of the interoperability between Autodesk Revit 2016 and EnergyPlus 8.4.0 by using Revit models for thermal simulations in EnergyPlus, one of the most commonly used tools for this purpose. The methodology consists of case studies targeting building models based on Case 600, from ASHRAE Standard 140, and Casa Eficiente Project, located in the city of Florianópolis, Brazil. The digital models of both buildings were produced in Revit with different modelling processes (conceptual mass or building elements with rooms or spaces) and software settings. All of these BIM models were exported in IFC, gbXML and IDF file formats and later converted through the use of additional tools in order to be opened in EnergyPlus. Such files were compared with the reference model of each building produced directly in EnergyPlus, using SketchUp containing the plug-in Legacy OpenStudio, in order to check for any distortions occurring in the process of data transfer when performing model exports and conversions. This comparison was based on parameters defined for geometry, simulation settings (materials thermal properties, building use and occupation etc.) and simulation results containing outputs of monthly internal temperatures for the thermal zones of each model. The results showed variations and similarities among the different types of modelling, export processes, and file formats used, revealing that distortions in data transfer become larger the more complex the building model is. This study points out conceptual mass models from gbXML files regardless of the export mode out of Revit as a viable alternative to be used in conjunction with EnergyPlus, as they preserve the geometrical accuracy of the building, even as some Revit default settings may be transferred over, thus failing to reflect some of the aspects of the real built environment. However, it was found that Revit models in general are not recommended for these types of exports due to the resulting rework needed for correcting files. It was concluded that the interoperability between Autodesk Revit and EnergyPlus is not perfect, as their combined use allows for data transfers that make possible the thermal simulation of buildings, however, in this exchange there are distortions in the exported geometries and lack of the necessary data for correct simulation in all exported models.